ADMINISTRASI PERSONALIA GURU DAN PEGAWAI - Metti Fathimah; Fadhilah Wardatul Muslimah; Fatimah Az Zahrah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Personnel administration of teachers and educational staff is a strategic aspect of educational management as it directly affects the quality of human resources in education. Teachers and educational staff, as key assets of educational institutions, must be managed in a professional, systematic, and sustainable manner. This article aims to examine the concept of personnel administration, the professionalism of teachers and educational staff, and the relationship between personnel administration and human resource development. This study employs a library research method by reviewing foundational theoretical books, national scientific journal articles, and other relevant literature. The findings indicate that personnel administration is not merely an administrative function but a managerial process that includes planning, recruitment, development, performance evaluation, and career advancement of teachers and educational staff.Effective personnel administration contributes to improved professionalism, job satisfaction, and performance of educational human resources, ultimately supporting the continuous improvement of educational quality.